Aromatic Plants of Tropical West Africa. Part XIV. Chemical and Biological Investigation of Lippia multiflora Mold. Essential Oil from Benin - AVLESSI, FÉLICIEN; ALITONOU, GUY ALAIN; Dominique C. K. Sohounhloue, Dominique C. K.; MENUT, Chantal; Bessière, Jean Marie (My University, 2005)
The essential oil of the leaves of Lippia multiflora collected in Benin was obtained by hydrodistillation and analyzed by capillary GC and GC/MS. Thirty-six components, representing 96.5% of oil were identified. The sample consisted mainly of monoterpenes. The major constituents were 1,8-cineole (39.9%), sabinene (11.1%), linalool (10.9%) and α-terpineol (10%). The antioxidant and antiradical activities of the oil was found to be low comparatively to that ofbutylated hydroxytoluene (BHT).
Keywords: Lippia multiflora; Verbenaceae; essential oil; 1; 8-cineole; antioxidant property; radical scavenging activity.